2017
DOI: 10.1186/s12879-017-2798-6
|View full text |Cite
|
Sign up to set email alerts
|

Rational use of Xpert testing in patients with presumptive TB: clinicians should be encouraged to use the test-treat threshold

Abstract: BackgroundA recently published Ugandan study on tuberculosis (TB) diagnosis in HIV-positive patients with presumptive smear-negative TB, which showed that out of 90 patients who started TB treatment, 20% (18/90) had a positive Xpert MTB/RIF (Xpert) test, 24% (22/90) had a negative Xpert test, and 56% (50/90) were started without Xpert testing. Although Xpert testing was available, clinicians did not use it systematically. Here we aim to show more objectively the process of clinical decision-making.First, we es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Excluding and confirming powers are not directly influenced by disease prevalence. 12 excluding power ¼ specificity 1 À sensitivity confirming power ¼ sensitivity 1 À specificity :…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluding and confirming powers are not directly influenced by disease prevalence. 12 excluding power ¼ specificity 1 À sensitivity confirming power ¼ sensitivity 1 À specificity :…”
Section: Introductionmentioning
confidence: 99%
“…Excluding and confirming powers are not directly influenced by disease prevalence. 12 The estimated probability of RR-TB in Mozambique was converted to odds and multiplied by the LRs of confirming arguments before testing. That result was multiplied with the excluding power of Xpert MTB+/RIF−.…”
Section: Introductionmentioning
confidence: 99%
“…Even when the Xpert MTB/RIF assay is available, empirical treatment remains highly prevalent in high TB burden countries [6]. The use of empirical treatment can be justi ed in these settings given the suboptimal performance of the Xpert assay, especially among smear negative individuals (sensitivity of 67%) and in people living with HIV (sensitivity of 80%) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that empiric treatment of Xpert Ultra patients did not increase the odds of survival, as survival was similar between those who did and did not receive empiric TB treatment (OR 1.28, 95% CI: 0.3-5.3). These results suggest that the recommendation by Kendall et al and by Decroo et al, that clinicians should continue to prescribe TB treatment for Xpert MTB/RIF-negative patients whose clinical presentations strongly suggest pulmonary in order to minimize a risk of TB related mortality[6,7] may no longer hold in the Xpert Ultra era. All participants in whom the clinician started empiric TB treatment had been assessed by chest radiography and had received a 'trial' of antibiotics (ceftriaxone and azithromycin, amoxicillin or vancomycin and doxycycline) to which they had not responded favorably.…”
mentioning
confidence: 99%
“…Because the sensitivity of the 1st generation Xpert assay is still suboptimal in smear-negative sputum samples (Churchyard et al, 2015;Decroo et al, 2017) the 2018 Ethiopian TB treatment guideline recommends that an antibiotic trial is performed when a TB diagnosis is in doubt. A course of broad-spectrum antibiotics with negligible Mtb activity is given to symptomatic Xpertnegative patients.…”
Section: Introductionmentioning
confidence: 99%